Effect of Densah Burs on Primary and Secondary Stability of Immediately Loaded Implants in Addition to Crestal Bone Loss and Gingival Probing Depth - An Evaluative Study - Shraddha Rathi; N D Gupta; Sarwar Hashmi; S Abirami; Faiz Noor Khan Yusufi (Wolters Kluwer Medknow Publications, 2024)
Introduction Osseodensification (OD) compaction increases primary stability by leaving the residual bone particles in the osteotomy site, which in turn act as an autograft.[1] Condensing the bone trabeculae through OD has demonstrated to have a potentiating influence on secondary stability.[2] Materials and Methods A split-mouth study was conducted in 40 patients to determine the effect of OD on implant success rate in terms of primary and secondary stability in situations including immediate loading of implants placed in low-density bone, which was tested using resonance frequency analysis (RFA) at the interval of 0, 6th month. In order to assess the implant success rate, gingival probing depth and crestal bone loss (CBL) around the implant were also assessed at baseline and 6 months. Results With respect to primary stability, at baseline, the mean RFA of Densah burs is 71.6 ± 9.5 and of conventional drills is 67.6 ± 10.4. The mean stability of Densah burs is significantly higher than conventional drills, both at baseline and after 6 months as well. CBL, at baseline, the mean CBL of Densah burs is 0.58 ± 0.11 and of conventional drills is 0.64 ± 0.12. The mean CBL of Densah burs is significantly lower than that of conventional drills for both. Conclusion The implant stability values found in the present study were remarkable when compared between OD and conventional osteotomy techniques. Decreased loss of bone at the crest probing depth also aided in the increased success rate.